DIASPORA, MEMORY, AND MOURNING IN THE FAREWELL AND HOW TO MAKE MILLIONS BEFORE GRANDMA DIES - Jordy Satria Widodo; Dyah Kristyowati; Muslim; Hilda Septriani; Shofiya Hafidza El Haq (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2026)
In an increasingly connected global world, film plays a crucial role in representing the complexities of Chinese diasporic identity and its accompanying emotional legacies. This study compares Lulu Wang's The Farewell (2019), representing the Chinese American community, with Pat Boonnitipat's How to Make Millions Before Grandma Dies (2024), focusing on the Sino-Thai community. Both films highlight the tension between tradition and modernity, as well as between family values ​​and economic pressures within contemporary capitalism. Drawing on Benedict Anderson's concept of the Imagined Community, this study analyzes how narrative structure, language use, and representations of death function as symbolic devices in constructing an imagined diasporic togetherness. The results show that The Farewell (2019) emphasizes identity fragmentation marked by linguistic alienation and emotional distance, while How to Make Millions Before Grandma Dies (2024) depicts a more connected form of family relations, albeit still influenced by the consumption and economic aspirations. Ultimately, both films represent the Chinese diaspora not only as an ethnic or geographical entity but as a construct of affective experiences born from collective practices of grief, care, and memory. Viewing cinema as an emotional and cultural archive, this study asserts that film demonstrates how diasporic communities continue to shape, negotiate, and reimagine their identities, losses, and legacies in an increasingly transnational world.